2005
DOI: 10.1111/j.1440-1746.2005.03837.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection in dialysis patients

Abstract: Hepatitis B virus (HBV) infection remains a major issue among dialysis patients. It is associated with a high risk of hepatic complication. The liver disease runs a unique clinical course in dialysis patients, as it can progress with modest hepatic inflammation and prominent fibrosis. The conventional cut-off level of serum alanine aminotransferase (ALT) for commencing antiviral therapy may prove too high and inappropriate for dialysis patients, and liver biopsy appears to be the only definitive means to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 81 publications
(145 reference statements)
1
46
1
2
Order By: Relevance
“…Jardim 19 Nonetheless, detecting such patients in hemodialysis clinics is of prime importance for avoiding dissemination of the virus inside these units, given that patients with unidentified occult HBV may transmit this infection to other patients as they undergo their treatment alongside other hemodialysis patients who are susceptible to HBV. The repeated exposure to body fluids during dialysis procedures predisposes dialysis patients to nosocomial transmission of HBV 25 . A molecular biological study on patients receiving treatment in the same hemodialysis units showed that there was relative homogeneity of HBV subtypes, which supports the notion that patient-to-patient transmission of HBV infection takes place in hemodialysis units 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Jardim 19 Nonetheless, detecting such patients in hemodialysis clinics is of prime importance for avoiding dissemination of the virus inside these units, given that patients with unidentified occult HBV may transmit this infection to other patients as they undergo their treatment alongside other hemodialysis patients who are susceptible to HBV. The repeated exposure to body fluids during dialysis procedures predisposes dialysis patients to nosocomial transmission of HBV 25 . A molecular biological study on patients receiving treatment in the same hemodialysis units showed that there was relative homogeneity of HBV subtypes, which supports the notion that patient-to-patient transmission of HBV infection takes place in hemodialysis units 25 .…”
Section: Discussionmentioning
confidence: 99%
“…in patients with ESRF undergoing dialysis has decreased significantly during the past few decades (1), it is still a distinct clinical problem, as the immunosuppressive nature of renal disease often leads to chronicity of the viral infection and results in an opportunity for nosocomial spread of the infection among dialysis patients (1)(2)(3)(4)(5). Occult HBV infection (OBI) is defined as the presence of a small amount of HBV in patients with serum that tests negative for hepatitis B surface antigen (HbsAg).…”
Section: Abu El Makarem Ma Et Al Occult Hepatitis B Virus In Hemodiamentioning
confidence: 99%
“…Infections with hepatitis B virus (HBV) and hepatitis C virus (HCV) are well-known and important causes of liver disease in end-stage renal failure (ESRF) patients on hemodialysis (HD) (1)(2)(3)(4). Although the prevalence of HBV…”
Section: Introductionmentioning
confidence: 99%
“…common than HCV in hemodialysis units (8)(9)(10)(11) due to routine screening, vaccination programs, infection control measures for HBV (12,13) and higher rates of viral clearance.…”
Section: Interprétationmentioning
confidence: 99%